Multibeam bathymetry raw data (Wärtsilä ELAC 3050 MK II entire dataset) of RV POSEIDON during cruise POS526, North Sea - Iason-Zois Gazis; Jens Greinert (PANGAEA, 2023)
The DeepSea Monitoring group (https://www.geomar.de/deepsea-monitoring) acquired high-resolution ship-based multibeam echosounder (MBES) data in the Tisler Reef region (North Sea) during the POS526 expedition SeASOM: Semi-Autonomous Subsurface Optical Monitoring for methane seepage and cold-water coral studies in the North Sea. The ELAC (Wärtsila) Seabeam 3050 was used at 50kHz. The data were recorded in .XSE format.SeASOM was run as part of the Helmholtz infrastructure project MOSES: Modular Observation Solutions for Earth Systems https://moses.geomar.de/ The dataset contains ancillary sound velocity profiles.